PENGARUH PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, ATTITUDE TOWARD USING TERHADAP BEHAVIORAL INTENTION TO USE PADA PENGGUNA NON TUNAI SHOPEEPAY DI YOGYAKARTA - Angellia Annakke Setiawan; Cahyani, Putri Dwi; Indraswari, Nurul Myristica (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the influence of perceived usefulness, perceived ease of use, and attitude toward using on behavioral intention to use among ShopeePay users in Yogyakarta. A quantitative approach was applied, with 170 respondents selected through purposive sampling, and data were analyzed using PLS-SEM with SmartPLS. The results show that perceived usefulness and perceived ease of use have no significant direct effect on behavioral intention to use, but both have a positive and significant effect on attitude toward using, which significantly affects behavioral intention to use and mediates the influence of both variables.